Protein kinase D2 modulates hepatic insulin sensitivity in male mice - Patricia Rada; Elena Carceller-López; Ana B. Hitos; Beatriz Gómez-Santos; Constanza Fernández-Hernández; Esther Rey; Julia Pose-Utrilla; Carmelo García-Monzón; Águeda González-Rodríguez; Guadalupe Sabio; Antonia García; Patricia Aspichueta; et al. (Molecular Metabolism)
Objectives: Protein kinase D (PKD) family is emerging as relevant regulator of metabolic homeostasis. However, the precise role of PKD2 in modulating hepatic insulin signaling has not been fully elucidated and it is the aim of this study. Methods: PKD inhibition was analyzed for insulin signaling in mouse and human hepatocytes. PKD2 was overexpressed in Huh7 hepatocytes and mouse liver, and insulin responses were evaluated. Mice with hepatocyte-specific PKD2 depletion (PKD2ΔHep) and PKD2fl/fl mice were fed a chow (CHD) or high fat diet (HFD) and glucose homeostasis and lipid metabolism were investigated. Results: PKD2 silencing enhanced insulin signaling in hepatocytes, an effect also found in primary hepatocytes from PKD2ΔHep mice. Conversely, a constitutively active PKD2 mutant reduced insulin-stimulated AKT phosphorylation. A more in-depth analysis revealed reduced IRS1 serine phosphorylation under basal conditions and increased IRS1 tyrosine phosphorylation in PKD2ΔHep primary hepatocytes upon insulin stimulation and, importantly PKD co-immunoprecipitates with IRS1. In vivo constitutively active PKD2 overexpression resulted in a moderate impairment of glucose homeostasis and reduced insulin signaling in the liver. On the contrary, HFD-fed PKD2ΔHep male mice displayed improved glucose and pyruvate tolerance, as well as higher peripheral insulin tolerance and enhanced hepatic insulin signaling compared to control PKD2fl/fl mice. Despite of a remodeling of hepatic lipid metabolism in HFD-fed PKD2ΔHep mice, similar steatosis grade was found in both genotypes. Conclusions: Results herein have unveiled an unknown role of PKD2 in the control of insulin signaling in the liver at the level of IRS1 and point PKD2 as a therapeutic target for hepatic insulin resistance.